Construction of emergency snow shelters using the results of air, snow and ground temperature measurements - Marcin Kalita; Stanisław Kędzia (Jan Długosz University in Częstochowa, 2023)
This paper presents the use of ground, snow, and air temperature measurements for the construction of makeshift snow shelters. In Poland, in the coldest places (the Tatra Mountains, the Orava Basin) the temperature values at the contact of the ground surface with the snow cover usually oscillate in the range from 0°C to −3°C. Therefore, when constructing snow shelters, a snow insulation layer should not be left on the ground inside the shelter, which blocks the heating of the shelter interior by the heat accumulated in the ground A very big influence on the temperature inside snow shelters is the size of the entrance opening and the height of its location. The larger the opening and the higher it is located in relation to the ground, the lower the temperature values and the greater the vertical thermal gradient occur inside the shelter. The temperature in a properly constructed snow shelter is regulated by covering the entrance hole. The thickness of the walls, and especially the roof of the shelter, should not exceed 40 cm. Walls with a thickness of 30 cm provide sufficient thermal insulation.